Clinical benefit of sodium-glucose transport protein-2 inhibitors in patients with heart failure: An updated meta-analysis and trial sequential analysis - Chen, Xiehui; Wang, Lili; Li, Huijun; Huang, Weichao; Huang, Siquan; Zhao, Lingyue; Guo, Wenqin (Frontiers in Cardiovascular Medicine, 2022)
To assess whether the current body of accumulated data can give convincing evidence in favor of sodium-glucose transport protein-2 inhibitor (SGLT-2i) in all types of heart failure (HF). We searched for randomized controlled trials contrasting the effectiveness of SGLT-2i to placebo or other hypoglycemic medications on clinicaltrials.gov, PubMed, and the Cochrane Library database. To gauge effect size, hazard ratios (HR) were employed as measurements. The composite outcome of cardiovascular death or hospitalization owing to HF was the primary endpoint. Eleven studies were included. In comparison to the control group, the data demonstrated that SGLT-2i is related with a decreased incidence of composite outcome (HR: 0.77, 95% CIs: 0.73–0.81, I2 = 0%, P < 0.01), CV death (HR: 0.87, 95% CIs: 0.81–0.94, I2 = 3%, P < 0.01), all-cause mortality (HR: 0.90, 95% CIs: 0.84–0.96, I2 = 10%, P < 0.01), and hospitalization due to HF (HHF) (HR: 0.70, 95% CIs: 0.66–0.75, I2 = 0%, P < 0.01). The trial sequential analysis found strong evidence of a decrease in the incidence of all clinical outcomes with SGLT-2i when compared to the control group. Subgroup analysis demonstrated that the association between SGLT-2i and clinical outcome was independent of population characteristics. We confirm that the present evidence supports the use of SGLT-2i in a wide range of HF patients. Systematic review registration [https://www.crd.york.ac.uk/prospero/#recordDetails], identifier [CRD42022333279].